2022
DOI: 10.1002/cam4.5380
|View full text |Cite
|
Sign up to set email alerts
|

hsa‐mir‐133a‐2 promotes the proliferation and invasion of cervical cancer cells by targeting the LAMB3‐mediated PI3K/ATK pathway

Abstract: Objective: Cervical cancer, one of the common types of malignant tumors progressed in women, is on the rise in developing countries. Numerous previous studies have demonstrated that hsa-mir-133a-2 miRNA is abnormally expressed in cervical cancer cells. However, its fundamental mechanism in cervical cancer needs to be further clarified. Our study set out to investigate the effect of hsa-mir-133a-2 on the phenotypes of cervical cancer cells as well as any potential molecular processes involved in the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…The GEP data presented in this study reveal, for the first time, the expression of MMP7, LAMB3 , and LAMC2 RNA in PTL. The epigenetic regulation of LAMB3 and LAMC2 , as previously reported in solid tumors, did not align with the findings of the current research 68 . Therefore, the findings presented necessitate additional large‐scale investigations.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The GEP data presented in this study reveal, for the first time, the expression of MMP7, LAMB3 , and LAMC2 RNA in PTL. The epigenetic regulation of LAMB3 and LAMC2 , as previously reported in solid tumors, did not align with the findings of the current research 68 . Therefore, the findings presented necessitate additional large‐scale investigations.…”
Section: Discussioncontrasting
confidence: 88%
“…The epigenetic regulation of LAMB3 and LAMC2, as previously reported in solid tumors, did not align with the findings of the current research. 68 Therefore, the findings presented necessitate additional large-scale investigations.…”
mentioning
confidence: 99%
“…We are not aware of studies at this time analysing the direct association between the purinergic receptor P2RY2 and PAAD; this receptor is known to upregulate selinexor, which, in turn, activates PI3K/AKT signalling in acute myeloid leukaemia ( Lin et al, 2022 ). It is well-known that abnormal activation of the PI3K-Akt signalling pathway is related to malignancy, there is also a relationship between PI3K and receptor tyrosine kinases upstream of PI3K ( Noorolyai et al, 2019 ), and furthermore, the KEGG pathway analysis of LM332-co-expressed gene revealed that a correlation with PI3K-Akt signalling pathway genes and numerous in vitro studies have linked LM332 with PI3K activation ( Yazlovitskaya et al, 2015 ; Zhang et al, 2019 ; Sui et al, 2022 ). Therefore, we suggest that the overexpression of LM332 in PAAD tumours represents a more widespread upregulation of genes promoting tumorigenesis poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a particular set of miRNAs (defined as epi-miRNAs) can indirectly affect the expression of tumor suppressor genes by influencing epigenetic mechanism effectors such as DNA methyltransferases, histone deacetylases, and polyoma suppressor complex genes, which are also controlled by epigenetic factors ( Fabbri and Calin, 2010 ). Further information on the mechanism underlying the occurrence of CC based on miRNAs has recently been obtained ( Sui et al, 2022 ). According to current findings, the mechanisms of miRNAs in CC development include the following aspects.…”
Section: Mirna Interference With CC Developmentmentioning
confidence: 99%